Pelatihan Virtual Laboratory Fisika Berbasis Pendekatan Saintifik untuk Melatih Literasi Sains Siswa - Roudhoutul Aulia Rochim; Noer Af’idah; Andri Wahyu Wijayadi; Oktaffi Arinna Manasikana; Nur Hayati; Fajrul Falah (Fakultas Sains dan Teknologi Universitas Kanjuruhan Malang, 2025)
This study aims to enhance students' science literacy through virtual Physics laboratory training using a scientific approach at Madrasah Aliyah Salafiyah Syafi'iyah Khoiriyah Hasyim Seblak. PhET simulations were selected to visualize abstract Physics concepts, such as sound waves, which are challenging to comprehend without physical laboratory tools. The activity involved 30 students in a series of training sessions, encompassing preparation, implementation, and evaluation phases. During the preparation phase, surveys and observations were conducted to identify challenges in Physics learning. The implementation phase included the delivery of materials, PhET simulation practices, and group discussions to deepen students' understanding. Evaluation was carried out by comparing students' understanding before and after the training. The results indicated that students were able to independently conduct virtual experiments, demonstrating their mastery of using PhET and achieving a better understanding of the material after utilizing this simulation. These findings highlight the potential of technology-based simulations to deepen students' understanding in Physics education, particularly in school environments facing challenges regarding laboratory facilities. This also opens opportunities for the development of technology-based education in madrasahs.